Phytopharmaceutical practices of traditional health practitioners in Burkina Faso: a cross-sectional study - Kampadilemba Ouoba; Hélène Lehmann; Arsène Zongo; Rasmané Semdé; Jean-Yves Pabst (BMC, 2023)
Abstract Background Traditional health practitioners constitute an important part of the health care system in Burkina Faso, particularly in the supply of traditional herbal medicines. Quality and safety of these medicines rely heavily on practices employed during their traditional development. However, traditional phytopharmaceutical practices are poorly described in Burkina Faso. This study aimed to describe the phytopharmaceutical practices of traditional medicine practitioners in Burkina Faso. Methods This was a cross-sectional descriptive ethno-pharmaceutical study, conducted from October 1 to November 30, 2020, among traditional practitioners in four randomly selected health districts: Nongr-Massom (Centre region), Tenkodogo (Centre-East region), Diapaga (East region) and Dafra (Hauts-Bassins region). An anonymous semi-structured face-to-face questionnaire was used to collect socio-demographic data and data on raw materials and finished products. Results Sixty-seven (67) traditional health practitioners, aged 56 years on average, including a majority of men (72%), participated in the study. Gathering of wild medicinal plants was the main source of raw materials acquisition (51.5%), which were usually leaves (32.3%). These raw materials were usually sun-dried (43.9%) and packaged mostly in plastic bags (37.2%). They were derived from 60 plant species belonging to 33 botanical families. Fabaceae was the most represented family (18.7%) and Khaya senegalensis Juss. (Meliaceae) the most cited plant species (5.2%). The finished products had an average shelf life of 17 months and were usually prepared as a decoction (31.7%) and administered most often orally (71.4%). Gastrointestinal disorders were the main predictable adverse events of the finished products (54%). Conclusion This study showed that THPs have important knowledge in the use of medicinal plants, but several shortcomings are observed in their phytopharmaceutical and plant protection practices. Continuous improvement of these practices, through education and training of traditional health practitioners, is essential for the conservation of plant biodiversity and quality assurance of traditional herbal medicines.